Family ownership, family identity of CEO, and accounting conservatism: evidence from Taiwan. Issue 4 (2nd October 2022) - Hsu, Hwa-Hsien; Tsao, Shou-Min; Lin, Che-Hung
ABSTRACT: This study investigates how variations in family ownership configurations and family identity of the CEO affect family firms' accounting conservatism in the East Asian economy, Taiwan. To address this objective, this study extends the traditional agency perspective and employs a socioemotional wealth framework. Findings document that family ownership is positively associated with family firms' accounting conservatism, whereas the degree of disparity between family cash flow and voting rights is negatively related to accounting conservatism. Additionally, family firms with a founder CEO are more likely to report conservatively than those with a descendent CEO. Our study expands the growing literature on how family owners' corporate governance features affect financial reporting decisions.